2021
DOI: 10.1177/07417136211027508
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of the COVID-19 Pandemic on Nontraditional Students’ Mental Health and Well-Being

Abstract: The current study sought to measure how the COVID-19 pandemic affected the mental health and well-being of college students, particularly nontraditional students. Participants ( n = 321) completed a series of surveys assessing their level of depression, anxiety, sleep disturbances, insomnia, and well-being. Participants also indicated their nontraditional student characteristics, level of resilience, and additional life stressors due to the pandemic. Statistical analyses found that participants reported higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…A type of individualised, meaningful exploration and discovery learning and deep learning is used in the field of education. To put it another way, learners build a new knowledge framework to enhance their own knowledge system by considering and critiquing new knowledge based on the original knowledge framework, integrating the old and the new, transferring, and verifying it [ 7 ]. A learning plan, which is an essential supporting tool in the teaching process, aims to develop students' capacity for independent learning and direct students in structuring their knowledge through questions, in line with the workings of deep learning.…”
Section: Introductionmentioning
confidence: 99%
“…A type of individualised, meaningful exploration and discovery learning and deep learning is used in the field of education. To put it another way, learners build a new knowledge framework to enhance their own knowledge system by considering and critiquing new knowledge based on the original knowledge framework, integrating the old and the new, transferring, and verifying it [ 7 ]. A learning plan, which is an essential supporting tool in the teaching process, aims to develop students' capacity for independent learning and direct students in structuring their knowledge through questions, in line with the workings of deep learning.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the Coronavirus pandemic, improved psychological well-being is influenced by a higher perception of meaningful living, and this differs in terms of gender [ 7 ]. Students with more work (business activity) and life experience after the COVID-19 pandemic reported lower levels of well-being and higher levels of depression and anxiety compared to pre-pandemic levels, but higher levels compared to all students [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Students chose different coping strategies. These negative symptoms were often more pronounced in female students than in male students [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stress and social isolation induced by the COVID-19 pandemic have led to an increase in levels of sleep disturbances and insomnia ( Babb et al, 2022 ; Lin et al, 2020 ), as well as rising rates of depression, anxiety, and stress ( Babb et al, 2022 ; Eysenbach et al, 2020 ; Kibbey et al, 2021 ). Social distancing and online classes have resulted in less social and emotional support for students from family, friends, classmates, and instructors ( Elmer et al, 2020 ).…”
mentioning
confidence: 99%
“…Previous findings tell us that, when faced with stressful events such as natural disasters and outbreaks of infectious disease, lack of control leads to people experiencing feelings of sadness, fear, anxiety, and anger, which can affect their long-term well-being, or current state of being healthy, happy, and comfortable ( Bai et al, 2004 ; Bults et al, 2011 ; Lau et al, 2008 ; Restubog et al, 2020 ; Thompson et al, 2017 ). Studies have already indicated increased levels of stress, anxiety, depression, and insomnia, and lowered well-being and sleep quality in college students due to the current pandemic ( Babb et al, 2022 ); therefore, it is expected that an increased proportion of students will display emotion dysregulation behaviors due to the overwhelming effects of COVID-19.…”
mentioning
confidence: 99%